EXTH-56. TARGETING GBM WITH AN ONCOLYTIC PICORNAVIRUS SVV-001 ALONE AND IN COMBINATION WITH FRACTIONATED RADIATION IN A NOVEL PANEL OF ORTHOTOPIC PDX MODELS. (14th November 2022) - Zhang, Huiyuan; Du, Yuchen; Qi, Lin; Xiao, Sophie; Braun, Frank K; Kogiso, Mari; Abdallah, Aalaa; Baxter, Patricia A; Su, Jack M; Brat, Daniel; Hallenbeck, Paul L; Teo, Wan-Yee; et al.
Abstract: BACKGROUND: Large panels of clinically relevant animal models are needed for the development of new therapies for GBM. SVV-001, a replication-competent oncolytic virus that can pass through the blood brain barrier, represents an attractive novel approach. Material and METHODS: Surgical tissues from 23 patients were implanted into the brains of NOD/SCID mice (1x10 5 cells/mouse) to develop patient-derived orthotopic xenograft (PDOX) models. Analysis of histology, gene expression (RNAseq), tumor growth was performed and compared with the patient tumors during subtransplantations (up to 5 passages). Anti-tumor activities of SVV-001 were examined in vitro in primary monolayer cultures, 3D neurospheres and purified glioma stem cells derived from 13 PDOX models; and its therapeutic efficacy validated in vivo in PDOX models through single i.v. injection (1x10 11 viral particle) alone and in combination with fractionated (2 Gy/day x 5 days) radiation. Changes of animal survival times were analyzed together with viral infection, cell proliferation and DNA damage. RESULTS: PDOX formation was confirmed in 17/23 (73.9%) GBMs. They replicated key histopathological features and diffuse invasion of the patient tumors. RNAseq identified the differentially expressed genes and subclassified PDOX models into proneural, classic and mesenchymal groups. SVV-001 killed primary monolayer cultures (4/13 models) and neurosphere (7/13 models) and putative glioma stem cells (CD133+ and/or CD15+ cells) in vitro, infected PDOX tumors without harming normal brain cells in vivo and significantly prolonged survival times in 2/2 models. Combination with radiation showed a trend in further prolonging animal survival times through enhanced DNA damages by SVV-001. CONCLUSION: A panel of 17 clinically relevant and molecularly annotated PDOX modes of GBM is developed. The strong anti-tumor activities of SVV-001 in vitro and in vivo in GBM models provided experimental rational that support the initiation of clinical trials in GBM patients.